The system of equations to be solved is:

4x + 8y - 4z = 4 ...(1)

3x + 6y + 5z = -13 ...(2)

-2x + y + 12z = -17 ...(3)

(1) + 2*(3)

=> 4x + 8y - 4z - 4x + 2y + 24z = 4 - 34

=> 10y + 20z = -30

=> y + 2z = -3

=> y = -3 - 2z

2*(2) + 3*(3)

=> 6x + 12y + 10z - 6x + 3y + 36z = -26 - 51

=> 15y + 46z = -77

substitute y = -3 - 2z

=> 15(-3 - 2z) + 46z = -77

=> -45 - 30z + 46z = -77

=> 16z = -32

=> z = -2

y = -3 - 2z = -3 + 2*2 = 1

x = 1 - 2y + z

=> 1 - 2 - 2

=> -3

**The solution of the system of equations is x = -3, y = 1 and z = -2**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now